A portable neuroprosthesis for applications in gait rehabilitations with stroke patients. (15th July 2011) - Sabut, Sukanta K.; Sikdar, Chanda; Singh, Priyanka; Kumar, Ratnesh; Manjunatha, M.
Neuroprosthesis (NP) is an emerging rehabilitation technique for replacing a function that is lost because of injury or disease of the central nervous system (CNS). A new, micro-controller-based portable neuromuscular stimulation device for drop-foot correction and other assistive applications has been developed with low cost. The portable stimulator features fully programmable, constant current, single-channel stimulation system. Rectangular stimulation intensity envelope algorithms are provided for drop foot correction and for other assistive applications. The effectiveness of functional electrical stimulation (FES) has been investigated in chronic hemiplegia. The reported benefits has shown, a significant reduction in physiological cost index (PCI), increasing walking speed, increasing step length, cadence, and reduction in composite spasticity score, accompanied by an increase in electromyogram analysis in the FES therapy group.